Frequency, Stressfulness and Type of Ethically Challenging Situations Encountered by Veterinary Team Members During the COVID-19 Pandemic - Quain, Anne; Mullan, Siobhan; McGreevy, Paul D.; Ward, Michael P. (Frontiers in Veterinary Science, 2021)
Ethically challenging situations (ECS) are common in veterinary settings and can lead to moral stress. However, there is no published information about how a global pandemic affects the frequency and types of ECS encountered by veterinary team members. An online mixed methods survey was developed to determine the frequency, stressfulness and types of ECS experienced by veterinarians, animal health technicians and veterinary nurses since the advent of the global COVID-19 pandemic in March 2020. Responses from 540 veterinary team members from 22 countries were analysed. With the advent of the COVID-19 pandemic, the mean frequency of ECS encountered by respondents increased from several times per month to several times per week (Spearman Rank Correlation 0.6189, P value <0.0001). The most common ECS (encountered at least several times per week) were: Challenging decisions about how to proceed when clients have limited finances (64.4%); Conflict between personal wellbeing and professional role (64.2%); Conflict between the interests of clients and the interests of their animals (63.3%); These were followed by Challenging decisions about what counts as an essential veterinary service (49.6%); Conflict between wellbeing of family/household members and professional role (46.2%); and Challenging decisions about whether to perform non-contact veterinary visits (46.2%). The most stressful ECS (reported to be very or maximally stressful) were: Conflicts between the interests of clients and the interests of their animals (50.2%); Conflicts between the interests of my employer and my own interests (42.4%); Challenging decisions about how to proceed when clients have limited finances (39.3%); Conflict between personal wellbeing and professional role (38.0%); and Conflict between wellbeing of family/household members and professional role (38.0%). Thematic analysis of free-text responses revealed that veterinary team members were particularly concerned about biosecurity, client financial limitations, animal welfare, working conditions, and client relations. The findings of this study identify the important need to prepare current and future veterinary team members for ethical challenges that may emerge in the context of global crises.